Gene Profiling in Patients with Systemic Sclerosis Reveals the Presence of Oncogenic Gene Signatures - Dolcino, Marzia; Pelosi, Andrea; Fiore, Piera Filomena; Patuzzo, Giuseppe; Tinazzi, Elisa; Lunardi, Claudio; Puccetti, Antonio (Frontiers in Immunology, 2018)
Systemic sclerosis (SSc) is a rare connective tissue disease characterised by three pathogenetic hallmarks: vasculopathy, dysregulation of the immune system and fibrosis. A particular feature of SSc is the increased frequency of some types of malignancies, namely breast, lung and haematological malignancies. Moreover, SSc may also be a paraneoplastic disease, again indicating a strong link between cancer and scleroderma. The reason of this association is still unknown, therefore we aimed at investigating whether particular genetic or epigenetic factors may play a role in promoting cancer development in patients with SSc and whether some features are shared by the two conditions. We therefore performed a gene expression profiling of peripheral blood mononuclear cells (PBMCs) derived from patients with limited and diffuse SSc, showing that the various classes of genes potentially linked to the pathogenesis of SSc (such as apoptosis, endothelial cell activation, extracellular matrix remodeling, immune response and inflammation) include genes that directly participate in the development of malignancies or that are involved in pathways known to be associated with carcinogenesis. The transcriptional analysis was then complemented by a complex network analysis of modulated genes which further confirmed the presence of signaling pathways associated with carcinogenesis. Since epigenetic mechanisms, such as microRNAs (miRNAs), are believed to play a central role in the pathogenesis SSc, we also evaluated whether specific cancer-related miRNAs could be deregulated in the serum of SSc patients. We focused our attention on miRNAs already found upregulated in SSc such as miR-21-5p, miR-92a-3p, and on miR-155-5p, miR 126-3p and miR-16-5p known to be deregulated in malignancies associated to SSc, i.e. breast, lung and haematological malignancies. miR-21-5p, miR-92a-3p, miR-155-5p and miR-16-5p expression was significantly higher in SSc sera compared to healthy controls. Our findings indicate the presence of modulated genes and miRNAs that can play a predisposing role in the development of malignancies in SSc and are important for a better risk stratification of patients and for the identification of a better individualized precision medicine strategy.